Pathways to a Sustainable Economy Bridging the Gap between Paris Climate Change Commitments and Net Zero Emissions (Springer International Publishing, 2018)
The focus of this edited volume is to identify challenges facing organizations in achieving zero greenhouse gas emissions by 2050 and a new energy economy, and to explore solutions from various sectors of the economy to enable the transition to a zero emissions future. Research presented here is divided into three parts, with an introductory statement on growth and sustainability. Part one discusses strategies towards a sustainable economy under a zero emissions goal. Part two contains industry specific case studies focusing on construction and related activities. Part three is devoted to country specific case studies from the Asia-Pacific region. Each of the chapters address one or more of the following issues: restoration, mitigation, adaptation and/or promoting resilience in the face of climate change as part of achieving a sustainable economy. The volume is multi-disciplinary in nature, drawing on various disciplines in social science, business, environment and policy, and will be of interest to UN development agencies, academic institutions, government policy makers, NGOs and business leaders.